Al-Muṣāḥabah Al-Lughawiyah Li Kalimah Al-Ḥubb wa Ṣiyaghuhā Fī Riwāyah Al-Ḥubb Al-Maktūm Muassasatan ‘ala Al-Mudawwanah Al-Lughawiyah - Syarif Husein; Moh Ainin; Yoke Suryadarma (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2021)
AbstractThe linguistic corpus is an old study in language learning that has been carried out by experts in their fields and continues to experience significant development along with the use of digital technology in the era of the industrial revolution 4.0. In linguistic analysis in Indonesia, the use of the linguistic corpus is still low. Corpus linguistic applications such as Sketch Engine, Lunchbox, AntConc, WordSmith, and other linguistic corpus applications have been developed. There is a lot of studies that using the linguistic corpus, and one of the linguistic studies is the study of the collocation. The study of collocation is an important study in language education to develop speaking skill and fluency. Accordingly, the researcher studied the collocation using the lorpus linguistic, and the researcher chose the Sketch Engine website as a data collection tool, so that it would be easier for the researcher to study the collocation of the word Al Hubb (love) in the novel Al Hubbul Maktum. The method this article uses a qualitative descriptive method, and the researcher conducted a library research to explain the forms of the word Al Hubb (love), the number of its appearance, and the forms of its collocations in the novel Al Hubbul Maktum. From this paper, the researcher found that the analysis of the collocations of the word Al Hubb (love) in the novel Al Hubbul Maktum using Corpus Linguistic can be done optimally and produce the forms of the word love and its collocations in the novel and then analyze it easily and faster. Accordingly, the researcher suggests that linguistic analysis for upgrading language skills using the Corpus Linguistic in Indonesia can be improved and developed so that it can turn into a new approach to teaching and learning Arabic.Keyword: Linguistic Corpus, study of collocations, language learning, Al Hubbul Maktum.